Pengaruh penggunaan pankreas sapi dan dua jenis bahan penyamak terhadap kualitas fisik kulit skrotum kambing - Titik Purwati Widowati; Agustini Suwarastuti; Amad Budi P (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2003)
The pancreas of cow was applied as bating agent for wet-salted scrotum skins of goat. The bated skins were then applied with vetetable tanning, chrome-agent and the combination of both agents. The tanned skins were analyzed their tensile strength and elasticity. The results showed that there were significant differencis on those parameters. The tensile strength and elasticity of chrome tanned, vegetable tanned, and the combination of chrome and vegetable tanned-skins were 107,75 kg/cm2 and 100,5%; 56,83 kg/cm2 and 27,83 %; and 52,28 kg/cm2 and 55,67% respectively. The tensile strength and elasticity of tanned skins indicated a tendency to increase when the concentration of cow pancreas was increased up to 1.5 % and decreased when the concentration reaches 2 % for chrome tanned skins. Keywords : cow pancreas, goat scrotum skin, vegetable tanning, chrome tanning.